2012
DOI: 10.1007/s00404-012-2609-7
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean section rate differences by migration indicators

Abstract: Migration status, source region, and time since migration are informative migration indicators for cesarean section risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 28 publications
0
30
0
1
Order By: Relevance
“…Twenty studies were removed because the comparison group included migrants, and/or the migrant group included native-born, and/or the assembly of the migrant and non-migrant groups were dissimilar. Seventy-six studies met the inclusion criteria and were assigned a quality score (see Table 1 for a complete description of included studies) [15-17,25-103]. Twenty-two studies were scored as good and 54 were scored as fair (see Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty studies were removed because the comparison group included migrants, and/or the migrant group included native-born, and/or the assembly of the migrant and non-migrant groups were dissimilar. Seventy-six studies met the inclusion criteria and were assigned a quality score (see Table 1 for a complete description of included studies) [15-17,25-103]. Twenty-two studies were scored as good and 54 were scored as fair (see Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Women from HSCs were less likely to have obstetric interventions or obstetric complications. Canadian research has reported higher cesarean delivery rates among primiparous resettled refugees compared with nonrefugee migrants from South‐East and Central Asia, but no difference between refugee and nonrefugee migrants from Africa . Higher cesarean delivery rates have also been reported among multiparous women of refugee background (especially from sub‐Saharan Africa) compared with their general maternity service population .…”
Section: Discussionmentioning
confidence: 99%
“…Both length of time in the receiving country and migration classification have been previously found to be predictors of unplanned cesarean births, but with varying effects based on migrants' region of origin . Migrants with a humanitarian status may be more vulnerable upon arrival and/or transition to poorer health more quickly because of their migration and/or resettlement experiences (i.e., more social exclusion, hardship, and experiences of discrimination) .…”
Section: Discussionmentioning
confidence: 99%